Konsep Gotong Royong dalam Tradisi Wuat Wa’i Desa Latung Manggarai Perspektif Heidegger: Sebuah Analisis Filsafat Metafisika - Jebar, Sirilus (Borneo Review, 2024)
This article focuses on the concept of mutual cooperation in the wuat wa’i tradition of Latung Manggarai Village in Heidegger's perspective. The concept of mutual cooperation is very strong and has even become a tradition that has been passed down from generation to generation in Latung Village Manggarai NTT. This concept is lived out in the tradition of wuat wa’i as a provision for travel in continuing school to the next level. In principle, for the Manggarai people, life is always related to other people. The purpose of this article is to understand and analyze the concept of gotong royong in the tradition of wuat wa’i in Latung Village Manggarai in Heidegger's perspective, as well as to find the relationship between the concept and Heidegger's metaphysical concepts. In compiling this article, the author uses a qualitative method in the form of descriptive-interpretative through literature sources from books, journals, and other reading sources both offline and online, which then become the author's critical notes and the author uses the interview method directly with several traditional leaders in Latung Village. The findings of this research show that the concept of mutual cooperation in the wuat wa’i tradition in Latung Village Manggarai has a deep and complex meaning in Heidegger's perspective. This concept can be connected to Heidegger's metaphysical concepts such as existence, being, and truth. In addition, the concept of gotong royong also has philosophical values that can be applied in everyday life. This concept shows that humans cannot live alone and need help from others to achieve their life goals. In Heidegger's perspective, the concept of mutual cooperation can be connected to the concept of das sein or human existence which is always in a relationship with others.